User conceptualizations of derivative relationships in the bibliographic universe. Issue 4 (3rd April 2018) - Tallerås, Kim; Dahl, Jørn Helge B.; Pharo, Nils
Abstract : Purpose: Considerable effort is devoted to developing new models for organizing bibliographic metadata. However, such models have been repeatedly criticized for their lack of proper user testing. The purpose of this paper is to present a study on how non-experts in bibliographic systems map the bibliographic universe and, in particular, how they conceptualize relationships between independent but strongly related entities. Design/methodology/approach: The study is based on an open concept-mapping task performed to externalize the conceptualizations of 98 novice students. The conceptualizations of the resulting concept maps are identified and analyzed statistically. Findings: The study shows that the participants' conceptualizations have great variety, differing in detail and granularity. These conceptualizations can be categorized into two main groups according to derivative relationships: those that apply a single-entity model directly relating document entities and those (the majority) that apply a multi-entity model relating documents through a high-level collocating node. These high-level nodes seem to be most adequately interpreted either as superwork devices collocating documents belonging to the same bibliographic family or as devices collocating documents belonging to a shared fictional world. Originality/value: The findings can guide the work to develop bibliographic standards. Based on the diversity of the conceptualizations, the findings also emphasize the need for more user testing of both conceptual models and the bibliographic end-user systems implementing those models.